Manajemen Keuangan Sekolah di TK Aisyiyah Nyai Ahmad Dahlan Full Day School - Atina Istiqomah (Kelola: Jurnal Manajemen Pendidikan, 2020)
This study aims to determine (1) sources of funds owned by TK Aisyiyah Nyai Ahmad Dahlan Full Day School, (2) financial management, (3) school financial administration, (4) school financial reports, (5) constraints in managing school finances, and (6) use of school finances. The research method uses descriptive analysis, this model describes the circumstances and phenomena obtained in the form of words so as to obtain a conclusion, this was revealed by Miles and Huberman. Data collection is used by observation, interview and document study, then the subject of research is the school treasurer. Data collection instruments using interview guides, observation guides and document study guides. In this study, researchers wanted to find out what was missing in school financial management at TK Aisyiyah Nyai Ahmad Dahlan Full Day School. The results of this study (1) the source of funds owned came from the Donation of Education Development (SPP), Committees and Re-Registration, funds from the Government such as BOP and BOSDA, (2) in financial management carried out by the school treasurer and then included in BMT, (3 ) there are 6 school administrations such as RAPBS books, general cash books, income subsidiary cash books, expenditure assistant cash books, financial statement books, and tuition fee cards, (4) financial management in schools starting from manual input and currently using computers and providing print out as proof of payment (5) school financial reports are carried out once a month and every year, (6) constraints faced when there is an urgent matter in making reports (7) the use of school finance for health, equipment money, learning facilities, environmental management, swimming and closing the year.